Challenges impacting on the quality of care to persons living with HIV/AIDS and other terminal illnesses with reference to Kanye community home-based care programme - Simon M Kang'ethe (Taylor & Francis Group, 2009)
HIV/AIDS has been found to be a challenging disease to humanity, its challenge spin-offs falling especially on to the caregivers of those infected and affected by the virus. This paper aims to discuss the challenges influencing the state of caregiving in the Kanye community home-based care (CHBC) programme in Botswana. The study was qualitative in design and explorative in nature, involving 82 primary caregivers in focus group discussions, and 5 CHBC nurses in individual interviews. Caregivers were found challenged by lack of community networks support, inadequate sanitary and care packages, poor shelter compromising privacy, inadequate income and food for their clients, inadequate care motivation as their volunteerism does not attract any payment, inadequate health personnel to offer psychosocial support like counselling, and an unconducive caring environment generally. Putting in place policies to redress caregivers' poverty, helping caregivers start income-generating projects, increasing community assistance and caregiving facilities are recommended as factors to address caregiver challenges.